A double-edged sword: cultural entrepreneurship and the mobilisation of morally tainted cultural resources. Issue 1 (2nd January 2019) - Dalpiaz, Elena; Cavotta, Valeria
ABSTRACT: We aim to highlight a type of cultural entrepreneurship, which has received scant attention by prior scholarship, and consists of deploying morally tainted cultural resources, i.e., resources that some audiences assess as going against accepted principles of morality. We argue that this type of cultural entrepreneurship is a double-edged sword and explain how it may ignite active opposition of offended audiences, as well as attract supportive audiences. We delineate a research agenda to shed light on whether, how, and with what consequences cultural entrepreneurs navigate such a tension – in particular how they (1) mobilise morally tainted cultural resources and with what effect on offended audiences; (2) deal with the consequent legitimacy challenges; and (3) transform moral taint into 'coolness' to enhance their venture's distinctiveness.